Evaluating the before operational stress program: comparing in-person and virtual delivery - Ioachim, Gabriela; Bolt, Nicole; Redekop, Michelle; Wakefield, Andrew; Shulhin, Andrii; Dabhoya, Jilani; Khoury, Juliana M. B.; Bélanger, Kathy; Williams, Sarah; Chomistek, Tessa; Teckchandani, Taylor A.; Price, Jill A. B.; et al. (Frontiers in Psychology, 2024)
Introduction Public safety personnel (PSP) are at increased risk for posttraumatic stress injuries (PTSI). Before Operational Stress (BOS) is a mental health program for PSP with preliminary support mitigating PTSI. The current study compared the effectiveness of delivering BOS in-person by a registered clinician (i.e., Intensive) to virtually delivery by a trained clinician (i.e., Classroom). Methods Canadian PSP completed the Intensive (n = 118; 61.9% male) or Classroom (n = 149; 50.3% male) program, with self-report surveys at pre-, post-, 1 month, and 4 months follow-ups. Results Multilevel modelling evidenced comparable reductions in anxiety (p < 0.05, ES = 0.21) and emotional regulation difficulties (ps < 0.05, ESs = 0.20, 0.25) over time with no significant difference between modalities. Participants discussed benefits of the delivery modality they received. Discussion The results support virtual delivery of the BOS program (Classroom) as an accessible mental health training option for PSP, producing effects comparable to in-person delivery by clinicians.